The Eurosystem's asset purchase programmes, securities lending and Bund specialness - Markus Baltzer; Kathi Schlepper; Christian Speck (Deutsche Bundesbank, 2022)
The Eurosystem's asset purchase programmes reduced the free float of German Bunds. Market participants feared impaired market functioning in the Bund market and monetary policymakers unintended consequences for monetary policy transmission. We study the intended and unintended consequences of asset purchases in the repo market with Bund collateral. Bunds that are eligible for APP purchases carry a repo specialness premium even when they are not purchased. This "eligibility premium" is larger than the actual flow effect of purchases identified in previous research. Securities lending (SecL) operations have a flow effect, but its magnitude is even smaller than the flow effect of APP purchases. Therefore, the impact of SecL in the repo market is only of a quite limited extent. Furthermore, the effects of APP and SecL on repo specialness are relatively small compared to those caused by banks' balance sheets window dressing at quarter ends and by the hedging pressure for Bund Futures.
Keywords: E43; E58; G12; G28; 330; Repos; Quantitative Easing; Securities Lending; Eurosystem; PSPP